Water Flow Through Saturated Clay Soil and Moisture Tension Relations as Affected by Ca-monobasic Phosphate Treatment - ASSEED, MOHAMED; ABDELGAWAD, GILANI; SHABAN, AHMED (The Libyan Journal of Agriculture, 2023)
The effect of Ca-monobasic phosphate addition to clay soil on the rate of water flow and moisture tension relations was examined under controlled laboratory experiment. The ca-monobasic phosphate was added to soil in two different rates, namely 0.05%, and 0.1% on weight basis. It was found that the addition of ca-monobasic phosphate changed slightly both the percent total pore space and pore size distribution. The data indicate that the change in moisture tension relation between treated and untreated soil was negligable. In the saturated water flow study it was found that the flow through the clay soil obtained from El Marj area did not follow the linear relationship of Darcy’s law. It was found that the saturated hydraulic conductivity value increased with higher applied hydraulic gradient. It was also observed that the flow through that clay soil could be described by the equation V = [0.86i + 0.228i2]10 2 where V is the flux in cm/hr and i is the hydraulic gradient. When ca-monobasic phosphate was added to the clay soil the pattern of flow was changed in two ways. First the flow in treated soil obeyed Darcy’s law linear relationship. The second effect was that the saturated hydraulic conductivity (K) decreased. For example in comparison with the untreated soil, there was 12% reduction in the value of K for the 0.05% treatment, while this reduction was 34% in the 0.1% treatment. This behaviour could be explained on the basis of possible reaction which affected the stability of porous material and passage of water in soil pores.